2008
DOI: 10.1016/j.brainres.2008.03.086
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold auditory inputs to extrastriate visual neurons are responsive to parametric changes in stimulus quality: Sensory-specific versus non-specific coding

Abstract: A new subthreshold form of multisensory processing has been recently identified that results from the convergence of suprathreshold excitatory inputs from one modality with subthreshold inputs from another. Because of the subthreshold nature of the second modality, descriptive measures of sensory features such as receptive field properties or location are not directly apparent as they are for traditional bimodal neurons. This raises the question of whether or not subthreshold signals actually convey sensory-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 39 publications
7
39
0
Order By: Relevance
“…For example, as shown in the present study (Experiment 1), the rat V2L cortex—a well-established area responsive to audiovisual stimuli (Toldi et al, 1986; Barth et al, 1995; Wallace et al, 2004; Hirokawa et al, 2008; Xu et al, 2014; Schormans et al, 2016)—is sensitive to differences in the timing of combined audiovisual stimuli, such that spiking activity was greatest during trials when the visual stimulus preceded the auditory by 20–40 ms (Figures 7C, 8C). These results are fairly consistent with previous studies that recorded audiovisual-evoked spiking activity in the superior colliculus (cat (Meredith and Stein, 1986, 1996; Meredith et al, 1987; Perrault et al, 2005, 2012; Stanford et al, 2005) and guinea pig (King and Palmer, 1985)) as well as multisensory cortices (cat PLLS (Allman and Meredith, 2007; Allman et al, 2008b, 2009) and cat FAES (Meredith and Allman, 2009)), and further confirm that the timing of the stimuli play a critical role in the ability of the neurons to integrate the different sensory modalities (King and Palmer, 1985; Meredith and Stein, 1986; Perrault et al, 2005; Stanford et al, 2005; Miller et al, 2015). Although the V2L cortex has been shown to play an important role in audiovisual processing, future investigations are needed in order to assess audiovisual temporal processing at the single neuron level.…”
Section: Discussionsupporting
confidence: 91%
“…For example, as shown in the present study (Experiment 1), the rat V2L cortex—a well-established area responsive to audiovisual stimuli (Toldi et al, 1986; Barth et al, 1995; Wallace et al, 2004; Hirokawa et al, 2008; Xu et al, 2014; Schormans et al, 2016)—is sensitive to differences in the timing of combined audiovisual stimuli, such that spiking activity was greatest during trials when the visual stimulus preceded the auditory by 20–40 ms (Figures 7C, 8C). These results are fairly consistent with previous studies that recorded audiovisual-evoked spiking activity in the superior colliculus (cat (Meredith and Stein, 1986, 1996; Meredith et al, 1987; Perrault et al, 2005, 2012; Stanford et al, 2005) and guinea pig (King and Palmer, 1985)) as well as multisensory cortices (cat PLLS (Allman and Meredith, 2007; Allman et al, 2008b, 2009) and cat FAES (Meredith and Allman, 2009)), and further confirm that the timing of the stimuli play a critical role in the ability of the neurons to integrate the different sensory modalities (King and Palmer, 1985; Meredith and Stein, 1986; Perrault et al, 2005; Stanford et al, 2005; Miller et al, 2015). Although the V2L cortex has been shown to play an important role in audiovisual processing, future investigations are needed in order to assess audiovisual temporal processing at the single neuron level.…”
Section: Discussionsupporting
confidence: 91%
“…Those multisensory studies used a paradigm that could, however, identify only the bimodal form of multisensory neuron. Using different search parameters that have been successful in identifying nonbimodal multisensory neurons in other areas [24,21], this study revealed that subthreshold forms of multisensory processing also occur in the FAES. These neurons were activated only by an auditory stimulus, but had that response significantly modulated by the presence of a seemingly ineffective visual stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…The studies reviewed here have been described in detail (Dehner et al, 2004; Meredith et al, 2006; Clemo et al, 2007; Allman and Meredith, 2007; Allman et al, 2008a and 2008b; Meredith and Allman, 2009) and were performed in compliance with the Guide for Care and Use of Laboratory Animals (NIH publication 86-23) and the National Research Council’s Guidelines for Care and Use of Mammals in Neuroscience and Behavioral Research (2003), approved by the Institutional Animal Care and Use Committee at Virginia Commonwealth University. The procedural elements of these studies are very similar to one another and, as such, permit a general comparison of their findings.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Neurons that are excited by stimuli from one modality, but have that activity modulated by an otherwise ineffective stimulus from another modality have been identified and termed subthreshold multisensory neurons (Allman and Meredith, 2007). This form of multisensory neuron has been identified in a variety of regions, including somatosensory areas SIV (Dehner et al, 2004) and rostral suprasylvian sulcal cortex (Clemo et al, 2007), auditory Field of the Anterior Ectosylvian sulcus (FAES; Meredith et al, 2006;Carriere et al, 2006; Meredith and Allman, 2009), and Posterolateral Lateral Suprasylvian (PLLS, Allman and Meredith, 2007; Allman et al, 2008b) and ferret Area 21 (Allman et al, 2008a) visual areas. The present investigation sought to evaluate the relative contribution of acoustically sensitive multisensory neurons (bimodal as well as subthreshold multisensory) in non-auditory areas to the dominant non-auditory activity of that area.…”
Section: Introductionmentioning
confidence: 99%